Diabetic Retinopathy: Animal Models, Therapies, and Perspectives - Xue Cai; James F. McGinnis (Journal of Diabetes Research)
Diabetic retinopathy (DR) is one of the major complications of diabetes. Although great efforts have been made to uncover the mechanisms underlying the pathology of DR, the exact causes of DR remain largely unknown. Because of multifactor involvement in DR etiology, currently no effective therapeutic treatments for DR are available. In this paper, we review the pathology of DR, commonly used animal models, and novel therapeutic approaches. Perspectives and future directions for DR treatment are discussed.